2016
DOI: 10.1177/1557988316652936
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Attentional Syndrome and Metacognitive Beliefs in Male Sexual Dysfunction: An Exploratory Study

Abstract: Erectile dysfunction (ED) and premature ejaculation (PE) are two forms of male sexual disorder with both psychological and physical features. While their cognitive, attentional, and affective components have been investigated separately, there is a lack of knowledge about the role played by cognitive attentional syndrome in their onset and maintenance. The aim of the present study was to investigate the possible contribution of perseverative thinking styles and thought control strategies to the development and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…15,18,19 Eventually, some men will avoid sexual activity, thereby maintaining or worsening the initial negative affect associated with sex. 19,21 A recent metaanalysis including 2,118 patients receiving internet-based cognitive behavior therapy has shown that more severe anxiety symptoms represent a crucial factor for successful positive ED outcomes. 22 In addition to cognitive distraction, negative automatic thoughts (eg, I am a failure, I need to perform, my erection is not firm enough) and macho-beliefs that involve unrealistic, unattainable expectations of male sexual performance (eg, penile erection is essential for a woman's sexual satisfaction, failing to get an erection may result in the woman leaving me) may predispose men to get trapped into a vicious circle of ED.…”
Section: Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…15,18,19 Eventually, some men will avoid sexual activity, thereby maintaining or worsening the initial negative affect associated with sex. 19,21 A recent metaanalysis including 2,118 patients receiving internet-based cognitive behavior therapy has shown that more severe anxiety symptoms represent a crucial factor for successful positive ED outcomes. 22 In addition to cognitive distraction, negative automatic thoughts (eg, I am a failure, I need to perform, my erection is not firm enough) and macho-beliefs that involve unrealistic, unattainable expectations of male sexual performance (eg, penile erection is essential for a woman's sexual satisfaction, failing to get an erection may result in the woman leaving me) may predispose men to get trapped into a vicious circle of ED.…”
Section: Evidencementioning
confidence: 99%
“…These homework assignments are regularly combined with cognitive interventions that challenge dysfunctional beliefs and expectations and aim at replacing these with more helpful thoughts. 21,24,26 In addition, men are prompted to search for new and extra sexual stimulation in order to vary and broaden their sexual script. This also involves nonintercourse forms of sexual stimulation to decrease their focus on penetration.…”
Section: Practical Approachmentioning
confidence: 99%
“…Previous research has consistently demonstrated that ED has a significant psychological impact on men, leading to feelings of emasculation or demasculinization, which are associated with depression, shame, decreased self-worth, and a fear of social stigma ( Takeuchi et al, 2021 ). In addition, studies have demonstrated that men with ED often experience heightened inhibition due to the fear of performance failure ( Sarin et al, 2014 ), resulting in avoidance of sexual activity and the perpetuation or worsening of negative emotional states associated with sex ( Giuri et al, 2017 ). Men with ED often attribute the erectile failures to personal incompetence (internal attribution) and perceive a lower sense of control or self-efficacy ( Rowland et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to sildenafil or cognitive behavioral therapy alone, the combination of cognitive behavioral therapy and sildenafil significantly improved the IIEF-EF score, with a higher success rate for treating ED within the first 4 weeks of therapy [75]. At the same time, PDE5is combined with cognitive behavioral therapy can both effectively improve ED and alleviate anxiety, depression and other mental problems, and the effect can be maintained for 15-18 months compared with PDE5is alone [31,76].…”
Section: Attention To Psychological Factorsmentioning
confidence: 99%